Implications of Behavioral Rules in Agent-Based Macroeconomics - Herbert Dawid; Domenico Delli Gatti; Luca Eduardo Fierro; Sebastian Poledna (CESifo GmbH, 2024)
In this paper we examine the role of the design of behavioral rules in agent-based macroeconomic modeling. Based on clear theoretical foundations, we develop a general representation of the behavioral rules governing price and quantity decisions of firms and show how rules used in four main families of agent-based macroeconomic models can be interpreted as special cases of these general rules. We embed the four variations of these rules into a calibrated agent-based macroeconomic framework and show that they all yield qualitatively very similar dynamics in business-as-usual times. However, the impact of demand, cost, and productivity shocks differ substantially depending on which of the four variants of the price and quantity rules are used.
Keywords: C63; E37; 330; agent-based macroeconomics; behavioral rules; pricing; forecasting